Isolation and Characterization of Sugarcane Root (Saccharum sp.) Rhizobacteria and Their Influence on the Growth of Lettuce Plants (Lactuca sativa L.) - Rismaningsih, Eka; Khumaira, Annisa; Nugraheni, Ika Afifah (BIOEDUKASI, 2024)
Lettuce (Lactuca sativa L.) is a horticultural commodity with good commercial value. Lettuce production is insufficient for consumer needs because of the excessive use of inorganic fertilizers, which reduce soil fertility. This research aims to decide rhizobacteria in the rhizosphere of sugarcane roots and their influence on increasing the growth of lettuce plants. The methods used are observational methods for taking composite soil samples. Macroscopic observations of bacterial colonies include the shape, elevation, edges, and color of the colonies produced. Through gram staining and physiological tests, including catalase, motility, carbohydrate fermentation, and indole tests, performed microscopic character observations. Field tests as PGPR were carried out on lettuce plants with treatment P0, P1, P2 and P3. The parameters observed were plant height, number of leaves, wet weight, dry weight, and root length. Based on the results of the research, the PGPR of sugarcane roots has rhizobacteria such as Corynebacterium sp, Terrabacter, Saccharococcus, Aeromicrobium, Paracoccus, Ancylobacter, Planococcus, and Azotobacter. PGPR affects the growth of lettuce plants, especially on plant height, number of leaves, and root length. Treatment P3 (PGPR 7.5 ml/L) and treatment P1 (2.5 ml/L) obtained the best concentrations, yielding optimal results on all test parameters. Treatments P0 and P2 did not have a significant effect on the growth of lettuce plants.